On mineral sovereignty: Towards a political theory of geological power. (November 2018) - Walker, Jeremy; Johnson, Matthew
Abstract: The Anthropocene thesis invokes the 'enormous geological power' of industrialism: driven by hydrocarbon combustion, manifest in planetary heating. Yet political theory has proceeded as if the organisation of geological power were incidental to history. Geological agency, we submit, is precisely what mining industries are organised to achieve, materially and politically. We propose mineral sovereignty as a term of method to analyse geological power in its legible, institutional and intentional forms. We deploy it to excavate an entwined genealogy of state and corporation: one evident in the constitutional (or extra-parliamentary) technologies of sovereignty and property that order the appropriation and distribution of mineral wealth. Through three provocations, we 'stratify' the concept of sovereignty: in the 'royal metals' of early modern states; in the rise of neoliberalism as a re-privatisation of mineral-energy infrastructures against the claims of social democracy; and in anticipatory extensions of mineral sovereignty to outer space. Mineral sovereignty discloses methodological problems for energy and climate policy. Pre-analytical distinctions between public law and the private power of fossil capital imply a hierarchy and separation that cannot be presumed, but must be achieved . We must 'leave it in the ground': this requires the re-assertion of democratic control over the mineral estate.